The Meaning of Live-In Activity Experience for the Self-Efficacy of Prospective Religious Teacher Students and Pastoral Practitioners - Nusa, Silvester; Lede, Imelda Vitrisia (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study explores the pastoral experience during live-in activities for Catholic Religious Education Program students and its impact on their self-efficacy as future religious teachers and pastoral practitioners. Using a descriptive qualitative method with a phenomenological approach, data were collected through semi-structured interviews with students involved in pastoral activities at St. Michael Elopada. The results show that students' self-efficacy increases through social support from the congregation, success in organizing and guiding pastoral activities, inspiration from community leaders who are experienced and respected figures, and belief in their potential. The live-in experience becomes a significant source of self-efficacy, boosting students' confidence in their duties as religious teachers and pastoral practitioners. This study's novelty lies in its focus on the pastoral field and using a phenomenological approach, demonstrating that social support and successful experiences can enhance self-efficacy. The contribution to the study is that social support and experiences of success can increase a person’s self-efficacy.